2004
DOI: 10.1182/blood-2003-11-3883
|View full text |Cite
|
Sign up to set email alerts
|

Durable responses after ibritumomab tiuxetan radioimmunotherapy for CD20+ B-cell lymphoma: long-term follow-up of a phase 1/2 study

Abstract: We previously demonstrated that yttrium-90 (Y-90) ibritumomab tiuxetan (Zevalin) radioimmunotherapy (RIT) was safe and effective for relapsed or refractory CD20 ؉ , B-cell, non-Hodgkin lymphoma (NHL). We now provide long-term follow-up data in responding patients based on International Workshop Response Criteria. Complete (CR), CR unconfirmed (CRu), and partial response (PR) rates were 29%, 22%, and 22%, respectively (overall response rate 73%, 51% in CR/CRu). Mean time to progression (TTP) and duration of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(98 citation statements)
references
References 7 publications
2
90
1
5
Order By: Relevance
“…In patients who achieved CR/CRu TTP was 24.7 months for RIT and 13.2 months for rituximab alone (Gordon et al, 2004b). Other phase II trials with 90 Y-ibritumomab tiuxetan reported CR/Cru rates between 15 and 51% (Wiseman et al, 2002;Witzig et al, 2002a;Gordon et al, 2004a) the follow-up being frequently shorter compared with the present study or that of Davies (Davies et al, 2004). Therefore, it is clear that both agents have demonstrated high levels of efficacy in patients with relapsed/refractory disease.…”
Section: Toxicitycontrasting
confidence: 46%
“…In patients who achieved CR/CRu TTP was 24.7 months for RIT and 13.2 months for rituximab alone (Gordon et al, 2004b). Other phase II trials with 90 Y-ibritumomab tiuxetan reported CR/Cru rates between 15 and 51% (Wiseman et al, 2002;Witzig et al, 2002a;Gordon et al, 2004a) the follow-up being frequently shorter compared with the present study or that of Davies (Davies et al, 2004). Therefore, it is clear that both agents have demonstrated high levels of efficacy in patients with relapsed/refractory disease.…”
Section: Toxicitycontrasting
confidence: 46%
“…The level for each attribute for individual treatment options was determined by reviewing the current literature on secondand third-line treatment options for patients with relapsed follicular lymphoma (Table 1). [6][7][8][9][10][11][12][13][14][15] As shown, the attributes included administration protocol, toxicity of the regimen, survival free of relapse and cost. Four categorical levels were used to describe the various administration protocols and toxicities for each treatment option.…”
Section: Questionnairementioning
confidence: 99%
“…[6][7][8] RIT provides targeted total body radiation treatment that is well tolerated, provides long-term disease control in 10-15% of patients, but is associated with median remission durations of B1 year. [9][10][11][12] Both auto-SCT and allo-SCT are only appropriate for younger, fit patients. Auto-SCT confers a significant PFS benefit over conventional CT, however, B50% of patients will relapse within 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated median time to progression (TTP) was 12.9 months. Long-term follow-up of this cohort demonstrated that many of these responses were durable, indeed 24% of responders had a TTP of more than 3 years (Gordon et al, 2004). In the pivotal phase III study, 143 rituximab naive patients with relapsed or refractory disease were randomized to receive either Y 90 ibritumomab tiuxetan or rituximab administered according to the standard schedule (Witzig et al, 2002b).…”
Section: Tositumomabmentioning
confidence: 99%